Pengembangan Bahan Ajar Elektronik Berbasis Representasi Multipel Menggunakan Inkuiri Terbimbing pada Topik Asam-Basa - Isni Nurani; Suyanta (Postgraduate, University of Mataram, 2024)
This study aims to develop and determine the feasibility of multiple representation-based electronic teaching materials using a guided inquiry model on the topic of acid and base for class XI high school. The method used in this research is research and development (R & D) which was developed by Thiagarajan and known as the 4D model. The 4D model consists of four stages: define, design, develop, and disseminate. This research instrument is a questionnaire to obtain a quantitative score used to determine the feasibility of teaching materials. The study results indicate that the developed teaching materials have a very good feasibility percentage. The developed teaching materials have been corrected by expert lecturers and revised according to the input given so that a decision is obtained that the teaching materials can be used. The feasibility of teaching materials is determined based on the assessment of the chemistry teacher as a reviewer and student responses. The assessment category obtained from the review by the chemistry teacher are very good with an average assessment percentage of 86.75%. Based on the results of field trials, the student responses show that the developed teaching materials were classified as very good category with an average percentage of 83.00%. Therefore, based on the validation and field trial results, the developed electronic teaching materials are feasible for use in class XI chemistry learning on the acid-base topic.